The Routledge companion to ethics - Skorupski, John, 1946- (London : New York : Routledge, 2010)
This is an outstanding survey of the whole field of ethics by a distinguished international team of contributors. The book opens with a comprehensive historical overview of ethics, including entries on Plato, Aristotle, Hume, and Kant.
History -- Ethical thought in china / Yang Xiao -- Ethical thought in India / Stephen Clark -- Plato and Socrates / Richard Kraut -- Aristotle / C.C.W. Taylor -- Later ancient ethics / A.A. Long -- The Arabic tradition / Peter Adamson -- Natural law / Knud Haakonssen -- Hobbes / Bernard Gert -- Ethics and reason / Mike LeBuffe -- Ethics and sentiment / Michael Gill -- Hume / James Harris -- Smith / Craig Smith -- Utilitarianism to Bentham / Fred Rosen -- Kant / Thomas Hill -- Hegel / Ken Westphal / Henry West -- Green, bradley and sidgwick / T.H. Irwin -- Nietzsche / Maudmarie Clark -- Pragmatist moral philosophy / Alan Ryan -- Existentialism / Jonathan Webber -- Heidegger /Stephen Mulhall -- Meta-ethics -- Ethics, religion, science / Simon Blackburn -- Freedom and responsibility / Randolph Clarke -- Reasons for action / Robert Audi -- Open question arguments / Thomas Baldwin -- Realism and its alternatives / Peter Railton -- Non-cognitivism / Alex Miller -- Error theory and fictionalism / Nadeem Hussain -- Cognitivism without realism / Andrew Fisher -- Relativism / Nick Sturgeon -- Ideas and methods from outside ethics -- Social anthropology / James Laidlaw -- Psychology / Jesse Prinz -- Biology / Michael Ruse -- Formal methods in ethics / Erik Carlson -- Ethics and law / John Gardner -- Perspectives in ethics -- Reasons, values and morality / Simon Robertson -- Consequentialism / Brad Hooker -- Contemporary kantian ethics / Andrews Reath -- Intuitionism / Philip Stratton-Lake -- Virtue ethics / Michael Slote -- Contractualism / Rahul Kumar -- Contemporary natural law theory / Anthony J. Lisska -- Feminist ethics / Samantha Brennan -- Ethics and aesthetics / Robert Stecker -- Morality -- Morality and its critics / Stephen Darwall -- Conscience / John Skorupski -- Recognition, respect / Allen Wood -- Blame, remorse, mercy, forgiveness / Christopher Bennett -- Evil / Geoffrey Scarre -- Responsibility : intention and consequence / Suzanne Uniacke -- Responsibility : act and omission / Michael Zimmerman -- Partiality and impartiality / John Cottingham -- Particularism and principles / Michael Ridge, Sean McKeever -- Debates in ethics / goals and ideals -- Welfare / Christopher Heathwood -- Ideals of living (perfectionism) / Vinit Haksar -- Justice -- Rights / Tom Campbell -- Justice and punishment / John Tasioulas -- Justice and distribution / M.G. Clayton -- Human life -- Life and death / Fred Feldman -- Ending life / R.G. Frey -- Our world -- Population / Tim Mulgan -- Animals / Alan Carter -- Environment / Andrew Brennan -- Current issues -- The ethics of free speech / Mary Kate McGowan -- The ethics of research / Julian Savulescu -- World poverty / Thomas Pogge -- War / Henry Shue -- Terrorism and torture / David Rodin.
Includes bibliographical references and index.
Keywords: Ethics